Ibn Khaldun’s theory, principles and concepts on urban planning - Nor Syafinaz Md. Safar,; Shamsul Azhar Yahya,; Ismar M.S. Usman,; Abdul Halim Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Ibn Khaldun was one of the most prominent Islamic scholars from Tunisia. He was very wise and futuristic and whose writings are still applicable to the current world. The objective of this article is to discuss the theories, principles and concepts formulated by Ibn Khaldun. His ideas gave rise to a new branch of science called social science today. Various theories were developed by Ibn Khaldun including urban planning. Other theories that he espoused were economic theory, development theory, concept of assabiyah, concept of urbanization, development of culture and civilization.